Clinical profile of tuberous sclerosis complex patients with and without epilepsy: a need for awareness for early diagnosis - Pereira, Conceição Campanario da Silva; Dantas, Felipe Diego Gomes; Manreza, Maria Luiza Giraldes de (Arquivos de Neuro-Psiquiatria, 2022)
Background Tuberous sclerosis complex (TSC) is a multisystemic disorder. Its clinical features manifest differently in several organs, prompting the need for better knowledge.Objective The goal of the present study is to evaluate the neurological findings of TSC, such as cerebral lesions and epilepsy, and to raise awareness of non-neurological findings that could contribute to an earlier diagnosis and treatment.Methods This was a natural history study of patients with a definitive diagnosis of TSC who were referred to a specialized outpatient clinic and followed-up for 2 years with clinical and radiological exams.Results A total of 130 TSC patients (59 males [45.4%], mean age 20.4 years old [1 to 56 years old]); 107 patients (82.3%) were diagnosed with epilepsy. Seizures predominantly began at < 1 year old (72.8%); focal seizures predominated (86.9%); epileptic spasms occurred in 34.5% of patients, and refractory epilepsy was present in 55.1%. Neuropsychiatric disorders, cortical tubers and cerebellar tubers were significantly more frequent in the epilepsy group. Moreover, rhabdomyomas were significantly more frequent in the epilepsy group (p = 0.044), while lymphangioleiomyomatosis was significantly less frequent in the epilepsy group (p = 0.009). Other non-neurological findings did not differ significantly between the groups with and without epilepsy.Conclusions The present study of TSC patients demonstrated the predominantly neurological involvement and significantly higher proportion of TSC-associated neuropsychiatric disorders in the epilepsy group. Higher proportions of cortical and cerebellar tubers may be a risk factor for epilepsy and neurodevelopmental disorders.
Keywords: Tuberous Sclerosis; Epilepsy; Early Diagnosis; Neurologic Manifestations; Neuropsychiatry